Selection of single chain antibody fragments binding to the extracellular domain of 4-1BB receptor by phage display technology - Salman Bagheri; Mehdi Yousefi; Elmira Safaie Qamsari; Farhad Riazi-Rad; Mohsen Abolhassani; Vahid Younesi; Ruhollah Dorostkar; Ali Akbar Movassaghpour; Zahra Sharifzadeh (Tumor Biology, 2017)
The 4-1BB is a surface glycoprotein that pertains to the tumor necrosis factor–receptor family. There is compelling evidence suggesting important roles for 4-1BB in the immune response, including cell activation and proliferation and also cytokine induction. Because of encouraging results of different agonistic monoclonal antibodies against 4-1BB in the treatment of cancer, infectious, and autoimmune diseases, 4-1BB has been suggested as an attractive target for immunotherapy. In this study, single chain variable fragment phage display libraries, Tomlinson I+J, were screened against specific synthetic oligopeptides (peptides I and II) designed from 4-1BB extracellular domain. Five rounds of panning led to selection of four 4-1BB specific single chain variable fragments (PI.12, PI.42, PII.16, and PII.29) which showed specific reaction to relevant peptides in phage enzyme-linked immunosorbent assay. The selected clones were successfully expressed in Escherichia coli Rosetta-gami 2, and their expression was confirmed by western blot analysis. Enzyme-linked immunosorbent assay experiments indicated that these antibodies were able to specifically recognize 4-1BB without any cross-reactivity with other antigens. Flow cytometry analysis demonstrated an acceptable specific binding of the single chain variable fragments to 4-1BB expressed on CCRF-CEM cells, while no binding was observed with an irrelevant antibody. Anti-4-1BB single chain variable fragments enhanced surface CD69 expression and interleukin-2 production in stimulated CCRF-CEM cells which confirmed the agonistic effect of the selected single chain variable fragments. The data from this study have provided a rationale for further experiments involving the biological functions of anti-4-1BB single chain variable fragments in future studies.